The "home country" of a multinational enterprise group facing insolvency - Mevorach, Irit (Cambridge University Press, 2008)
Identifying the ‘home country’ for the multinational enterprise group’s insolvency proceedings can be crucial for allowing an effective insolvency process for related entities. However, this is a challenging task given the diversity of group structures and insolvency scenarios. This article attempts to deal with this issue by applying alternatives of ‘insolvency venues’ to the group case and confronting them with key insolvency goals, to assess which standard venue could most effectively enhance cost efficiency, predictability and transparency of the rules (regarding jurisdiction), control forum shopping and accord with creditors’ legitimate expectations. The paper suggests that operational headquarters is in principle the most efficacious test for multinational groups, yet it also points out its limitations.